Molecular Dynamics Study on the Distributed Plasticity of Penta-Twinned Silver Nanowires - Lee, Sangryun; Ryu, Seunghwa (Frontiers in Materials, 2015)
The distributed plasticity of pentatwinned silver nanowires has been revealed in recent computational and experimental studies. However, the molecular dynamics (MD) simulations have not considered the imperfections seen in experiments, such as irregular surface undulations, the high aspect ratio of nanowires, and the stiffness of loading devices. In this work, we report the effect of such inherent imperfections on the distributed plasticity of penta-twinned silver nanowires in MD simulations. We find that the distributed plasticity occurs for nanowires having undulations that are less than 5% of the nanowire diameter. The elastic stress field induced by a stacking fault promotes the nucleation of successive stacking fault decahedrons (SFDs) at long distance, making it hard for necking to occur. By comparing the tensile simulation using the steered molecular dynamics (SMD) method with the tensile simulation with periodic boundary condition (PBC), we show that a sufficiently long nanowire must be used in the constant strain rate simulations with PBC, because the plastic displacement burst caused by the SFD formation induces compressive stress, promoting the removal of other SFDs. Our finding can serve as a guidance for the molecular dynamics simulation of crystalline materials with large plastic deformation, and in the design of mechanically reliable devices based on silver nanowires.